Depolarization ratio of polar stratospheric clouds in coastal Antarctica: comparison analysis between ground-based Micro Pulse Lidar and space-borne CALIOP observations - C. Córdoba-Jabonero; J. L. Guerrero-Rascado; D. Toledo; M. Parrondo; M. Yela; M. Gil; H. A. Ochoa (Atmospheric Measurement Techniques, 2013)
Polar stratospheric clouds (PSCs) play an important role in polar ozone depletion, since they are involved in diverse ozone destruction processes (chlorine activation, denitrification). The degree of that ozone reduction is depending on the type of PSCs, and hence on their occurrence. Therefore PSC characterization, mainly focused on PSC-type discrimination, is widely demanded. The backscattering ( R ) and volume linear depolarization (δ V ) ratios are the parameters usually used in lidar measurements for PSC detection and identification. In this work, an improved version of the standard NASA/Micro Pulse Lidar (MPL-4), which includes a built-in depolarization detection module, has been used for PSC observations above the coastal Antarctic Belgrano II station (Argentina, 77.9° S 34.6° W, 256 m a.s.l.) since 2009. Examination of the MPL-4 δ V feature as a suitable index for PSC-type discrimination is based on the analysis of the two-channel data, i.e., the parallel (p-) and perpendicular (s-) polarized MPL signals. This study focuses on the comparison of coincident δ V -profiles as obtained from ground-based MPL-4 measurements during three Antarctic winters with those reported from the space-borne lidar CALIOP (Cloud-Aerosol Lidar with Orthogonal Polarization) aboard the CALIPSO (Cloud-Aerosol Lidar and Infrared Pathfinder Satellite Observation) satellite in the same period (83 simultaneous cases are analysed for 2009–2011 austral winter times). Three different approaches are considered for the comparison analysis between both lidar profile data sets in order to test the degree of agreement: the correlation coefficient (CC), as a measure of the relationship between both PSC vertical structures; the mean differences together with their root mean square (RMS) values found between data sets; and the percentage differences (BIAS), parameter also used in profiling comparisons between CALIOP and other ground-based lidar systems. All of them are examined as a function of the CALIPSO ground-track distance from the ...